2012
DOI: 10.1073/pnas.1207911109
|View full text |Cite
|
Sign up to set email alerts
|

Cold but not sympathomimetics activates human brown adipose tissue in vivo

Abstract: As potential activators of brown adipose tissue (BAT), mild cold exposure and sympathomimetic drugs have been considered as treatments for obesity and diabetes, but whether they activate the same pathways is unknown. In 10 healthy human volunteers, we found that the sympathomimetic ephedrine raised blood pressure, heart rate, and energy expenditure, and increased multiple circulating metabolites, including glucose, insulin, and thyroid hormones. Cold exposure also increased blood pressure and energy expenditur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
234
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 278 publications
(267 citation statements)
references
References 34 publications
19
234
4
Order By: Relevance
“…In our study, metabolically active BAT was found with 18 F-FDG PET-CT in 80% of all participants after 2 h of cold exposure (16-18°C), which is in line with previous publications [8]. Furthermore, the median SUV max of 18 F-FDG in BAT is similar to values reported by Cypess et al, who also investigated BAT activity in lean, healthy men [16].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In our study, metabolically active BAT was found with 18 F-FDG PET-CT in 80% of all participants after 2 h of cold exposure (16-18°C), which is in line with previous publications [8]. Furthermore, the median SUV max of 18 F-FDG in BAT is similar to values reported by Cypess et al, who also investigated BAT activity in lean, healthy men [16].…”
Section: Discussionsupporting
confidence: 80%
“…our ROI). Cypess et al used the same threshold [16]. However, Vosselman et al used a threshold of 1.5 g/ml [17] and van Marken Lichtenbelt et al reported that they used a 'set threshold' [8], whereas Carey et al and Ouellet et al considered an SUV >1.0 g/ml as BAT [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…Because glucose is not the primary substrate, BAT activity based on [ 18 F]FDG uptake may underestimate and potentially miss components of BAT energy metabolism under certain physiological conditions. While [ 18 F]FDG-PET-based assessments of human BAT activity in response to acute [20,21,38,42] and chronic [2,4] cold exposure have reflected the expected outcomes based on rodent experiments, this study indicates that there are species differences for other adaptive stimuli. Although we have shown that pioglitazone reduced coldstimulated BAT glucose uptake, we cannot definitively claim that fat oxidative capacity also decreased.…”
Section: Methodological Strengths and Limitationsmentioning
confidence: 98%
“…This study consisted of two parts: (1) a human primary cell culture study to determine whether pioglitazone could induce adipogenesis and browning of primary adipocytes derived from subacromioclavicular adipose biopsies and (2) upon determination that pioglitazone induced browning in vitro, a clinical trial to examine whether prolonged (4 weeks) treatment of humans with pioglitazone would increase coldstimulated BAT activity, assessed by glucose uptake using [ 18 [20,21] and would therefore be expected to contain a mixture of adipocyte and pre-adipocyte subtypes, including brown/beige adipocytes, and is directly relevant to informing our subsequent clinical trial in which upper thoracic and cervical adipose tissue is the primary region of interest.…”
Section: Overviewmentioning
confidence: 99%
“…In humans it is currently not known whether a pharmacological agent can activate BAT, as previous studies have used inconclusive experimental techniques [9,20,21] or observed no effect of drugs on BAT activity [22,23]. Since BAT activation is mediated by sympathetic efferents predominantly via β-adrenergic receptors in BAT [1], sympathomimetic drugs represent a relevant drug class for investigation.…”
Section: Introductionmentioning
confidence: 99%